MANNER ADVERB PLACEMENT IN ENGLISH, SPANISH AND LITHUANIAN: A CORPUS-BASED APPROACH - Dičpinigaitytė, Aušra; Korostenskienė, Julija (Verbum, 2015)
The present study is concerned with a quantitative analysis of six manner adverbs in English and their translation equivalents in Spanish and Lithuanian. As is known, within the generative syntactic framework, manner adverb placement is regarded as a basic diagnostic tool used to define the position of the verb on the syntactic tree. The study uses Rochette’s (1990) classification of adverbs into six classes, depending on a range of possible positions: Initial, VP-external/Aux, or VP-internal. The corpus study of the selected group of manner adverbs has revealed that, traditionally regarded as the lowest, the English manner adverbs well and fast are not confined to VP-internal position and can also precede the verb, which suggests that they might be positioned higher in the adverb hierarchy than traditionally assumed. The findings also reveal that manner adverbs in Spanish and Lithuanian may take different positions from their English counterparts and can therefore be assigned to different adverb classes. For example, English and Spanish manner adverbs belong to Class IV in Rochette’s classification, whereas their Lithuanian counterparts exhibit features of Class I adverbs. The study shows that English and Spanish manner adverbs most frequently appear in two positions, pre- and post verbally, whereas their distributional diversity is greatest in Lithuanian, which might be due to issues related to the information structure of the language.